The dynamics of RNA participation in the vitellogenesis of Rhipicephalus sanguineus ticks Latreille 1806 (Acari: Ixodidae). I. Nucleoli or Cajal bodies? - Camargo Mathias, Maria Izabel; Arnosti, Andre; Brienza, Paula Desjardins; Furquim, Karim Christina Scopinho; de Oliveira, Patricia Rosa; Denardi, Sandra Eloisi; Bechara, Gervasio Henrique [UNESP] (My University, 2010)
To understand the morphological and histological aspects of internal systems of ticks has become important matter since these arthropods have an impact in the areas of the economy and public health. In this context, this study has provided morphological data on female germinative cells of Rhipicephalus sanguineus ticks, ectoparasites of dogs that maintain a close relationship with human on a daily basis. Oocytes of engorged females were analyzed, through the PAS reaction (detection of polysaccharides) counterstained by methyl green (detection of RNA) revealing information that allowed to infer for the first time the presence of Cajal bodies, in the germinal vesicles (nuclei) of developing oocytes, as well as showing how the RNA and the polysaccharides are involved in the dynamics of the vitellogenesis in this species. [copyright] 2010 Elsevier Ltd. All rights reserved.